PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SDN 007 PEDAMARAN - Jumarni '; Eddy Noviana; Zufriady ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research intent to increase IPA studying result student by applying kooperatif learning model type Jigsaw on student class IV SDN 007 Pedamaran. This research up on its low usufructs student studying class IV SDN 007 Pedamaran. Initially just 11 student that reaches KKM of 25 students. One of its low cause usufructs this IPA studying at because karean in processes more teacher learning a lot of utilize discourse method and noting even, so quick student goes against the stomach in studying. This observational form is Observational Action braze (PTK). Subjek is research is student class IV SDN 007 Pedamaran. Observational procedure is utilize cycle model. Each cycle consisting of four phases, which is: planning, performing, watch and reflection. Data source comes from to learn and student. Data collecting tech is observation and documentation. Base to essay studying result, available result step-up studies IPA SDN'S student 007 Pedamaran in each its cycle. Average value on cycle i. to reach 71 and on cycle II. which is 84,6. klasikal's learned thoroughness on i. cycle which is 64%, complete student 16 and that don't complete 9. On cycle II. which is 92%, complete student 23 and that don't complete 2. Step-up usufruct to study IPA Dikuti even with teacher skill and student activity that increases. Skill learns on i. cycle to be gotten percentage average 75%, and on cycle II. acquired percentage average 91,66% includes in kualifikasi very good. Meanwhile step-up percentage usufructs to study on i. cycle 17,94% and on cycle II. 40,53%.Key Word : Kooperatif Model Type Jigsaw , IPA Learned Result